2007
DOI: 10.1186/1472-6963-7-161
|View full text |Cite
|
Sign up to set email alerts
|

Patients' satisfaction and opinions of their experiences during admission in a tertiary care hospital in Pakistan – a cross sectional study

Abstract: Background: It is often felt that developing countries need to improve their quality of healthcare provision. This study hopes to generate data that can help managers and doctors to improve the standard of care they provide in line with the wishes of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
2
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 8 publications
3
37
2
3
Order By: Relevance
“…There is evidence that if the consent process is communicated properly patient satisfaction levels during and after surgery are higher (19,20). Taking consent at the appropriate time and in the correct manner can resolve many issues after surgery (21,22). This was evident from the results of our study, in which a majority of the patients (86.5%) and their relatives (78.4%) wanted to have detailed information about the surgery.…”
Section: Discussionsupporting
confidence: 68%
“…There is evidence that if the consent process is communicated properly patient satisfaction levels during and after surgery are higher (19,20). Taking consent at the appropriate time and in the correct manner can resolve many issues after surgery (21,22). This was evident from the results of our study, in which a majority of the patients (86.5%) and their relatives (78.4%) wanted to have detailed information about the surgery.…”
Section: Discussionsupporting
confidence: 68%
“…For example dissatisfaction with instructions related to treatment reflects a distrust of doctors. Education needs to be directed at helping doctors gain the trust of patients [31].…”
Section: ‫املتوسط‬ ‫لرشق‬ ‫الصحية‬ ‫املجلة‬ ‫عرش‬ ‫الثامن‬ ‫املجلد‬ ‫mentioning
confidence: 99%
“…12 Imam et al, study very few patients reported any degree of dissatisfaction with the cleanliness of the wards or the washrooms. 15 Our study suggests that it is below satisfaction level because 80.5% surgical patients claimed that the cleanliness of the bathrooms was poor.…”
Section: Discussionmentioning
confidence: 78%